Angka Kejadian Diare Pada Balita - Ekawati; Susi Susanti (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: According to the World Health Organization (WHO), diarrhea is the second leading cause of death ininfants. According to the results Riskesdas 2007, diarrhea is the number one cause of death in children under five(25.2%). Based on PHO reporting cases of diarrhea DIY highest in Kulon Progo by the number of 25 491 diarrheacases were handled. Data from the Health Department Kulon Progo 2015. Most cases of diarrhea are at the healthcenter Sentolo 1, 2015 found 242 children under five.Objective: To determine the incidence of diarrhea in children under five in Puskesmas Sentolo I Kulon Progo during 2015.Methods: This study is descriptive quantitative, with retrospective time approach. Data collection tools using medical record using secondary data. The subjects all under five with diarrhea in 2015 amounted to 102 infants.Results: Of the 102 respondents mostly under five with diarrhea aged 1-3 years (77.5%), gender is male (52.9%),good nutritional status (73.5%), and had diarrhea without dehydration of (80.4%).Conclusion: Of the 102 respondents mostly children under five with diarrhea majority aged 1-3 years with malegender, good nutritional status and had diarrhea without dehydration.Keywords: Genesis Diarrhea, Toddler